2020
DOI: 10.1016/j.sleh.2020.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Associations between positive and negative social media experiences and sleep disturbance among young adults

Abstract: Objectives:We sought to examine the association of positive and negative experiences using social media (SM) and sleep disturbance in a national survey of U.S. young adults. Methods: Experiences using social media were assessed with 2 items asking participants about the percentage of time using SM that involved a negative/positive experience that they were personally involved in. Sleep disturbance was assessed using the validated PROMIS 4-item short form. Ordinal logistic regression was used to examine associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In this context, scholars contend that the knowledge of social media's dark side can be enriched by further diagnosing such manifestations and their mutual dynamics (e.g., Royant-Parola et al, 2018;Tandon et al, 2020). For instance, the association between the compulsive use of social media and problematic sleep, which has so far been under-explored, can offer useful insights (e.g., Milyavskaya et al, 2018;Rzewnicki et al, 2020).…”
mentioning
confidence: 99%
“…In this context, scholars contend that the knowledge of social media's dark side can be enriched by further diagnosing such manifestations and their mutual dynamics (e.g., Royant-Parola et al, 2018;Tandon et al, 2020). For instance, the association between the compulsive use of social media and problematic sleep, which has so far been under-explored, can offer useful insights (e.g., Milyavskaya et al, 2018;Rzewnicki et al, 2020).…”
mentioning
confidence: 99%
“…Given the relatively recent growth in social media use in the United States, research conducted on the effects of social media on mental health outcomes found that the content and quality of social media experiences and interactions may be important to our understanding of the roles of social media in myriad mental health outcomes [ 15 - 18 ]. For LGB persons, negative social media experiences may play a critical role in depression disparities.…”
Section: Introductionmentioning
confidence: 99%